2009
DOI: 10.1359/jbmr.081101
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Glucocorticoids on Cortical and Trabecular Compartment BMD in Childhood Nephrotic Syndrome

Abstract: Glucocorticoid (GC) effects on skeletal development have not been established. The objective of this pQCT study was to assess volumetric BMD (vBMD) and cortical dimensions in childhood steroid-sensitive nephrotic syndrome (SSNS), a disorder with minimal independent deleterious skeletal effects. Tibia pQCT was used to assess trabecular and cortical vBMD, cortical dimensions, and muscle area in 55 SSNS (age, 5−19 yr) and >650 control participants. Race-, sex-, and age-, or tibia length–specific Z-scores were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
72
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 55 publications
7
72
2
1
Order By: Relevance
“…However, we did observe a decrease in BMD at the spine (a trabecular-rich site) but increased cortical thickness at the second metacarpal. Our results are therefore in line with previous reports [30,31] suggesting disparate effects of GCs on cortical and trabecular sites.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, we did observe a decrease in BMD at the spine (a trabecular-rich site) but increased cortical thickness at the second metacarpal. Our results are therefore in line with previous reports [30,31] suggesting disparate effects of GCs on cortical and trabecular sites.…”
Section: Discussionsupporting
confidence: 94%
“…In a recent study using peripheral quantitative computed tomography (pQCT) at the tibia, GC-treated children with NS showed greater cortical volumetric BMD and cortical area, and lower trabecular volumetric BMD compared to controls [30]. Similar results were reported by Hegarty et al, who found by pQCT a significant reduction in distal radial trabecular volumetric BMD, but no reduction in total volumetric BMD in young adults who had NS during childhood [31].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is important, since DXA does not differentiate between these two structures, yet studies have shown divergent effects of GC on the two compartments [41]. Tsampalieros et al [42] recently studied a longitudinal cohort of pediatric NS treated with a similar initial GC regime as in our study, and found that tibia trabecular volumetric BMD Z-scores were lower and cortical density and area Z-scores higher compared to controls around the time of diagnosis.…”
Section: Discussionmentioning
confidence: 51%
“…The higher cortical density was associated with higher GC doses, attenuated growth in tibial length and declines in cortical area Z-scores. Higher cortical density in GCtreated disorders has been observed in other cohorts [27,41] and is attributed to low bone turnover giving rise to prolongation of the secondary mineralization phase. With improvement in bone turnover, cortical density appears to normalize [27], suggesting the abnormally high cortical density may not necessarily confer increases in bone strength.…”
Section: Discussionmentioning
confidence: 59%